Effect of condenser spray cooling on the performance of refrigerant pump heat pipe composite air conditioners - HUANG Xiang; WANG Xin; CHU Junjie; SU Lin; YAN Libo; YANG Liu; HU Jian (Xi'an Gongcheng Daxue xuebao)
To reduce the energy consumption of the refrigeration system of the data center and solve the problem of high power consumption of refrigerant pump heat pipe composite air conditioner in summer, the energy efficiency of the unit was improved by installing a spray cooling device on the outside of the condenser, and the performance research and applicability analysis were carried out under different working conditions and in various cities. The results show that the total refrigeration power of fluorine-pump heat pipe composite air conditioner was reduced from 3.44, 4.51, and 6.48 kW to 2.81, 3.66, and 4.89 kW, under the conditions of at 15 ℃, 25 ℃, and 35 ℃ outdoor temperatures, and the energy efficiency ratio (EER) increased by 13.4%, 27%, and 30.7%, respectively, compared with that without spray cooling device. Further analysis shows that in the five typical cities of Harbin, Beijing, Kunming, Shanghai, and Guangzhou, the annual energy efficiency ratio (AEER) increased by 4.16%, 6.69%, 9.88%, 10.76%, and 19.65% respectively. The EER improvement rate of air conditioning increased with outdoor temperature. The energy-saving effect was more significant in cities with a large proportion of medium and high-temperature duration.